Socio-Economic Status and Mental Health on The Academic Learning Achievement of Final-Year Students - Kamalia, Putri Ulfa; Nugrohoseno, Dwiarko; Untarini , Nindria; Puspasari, Durinda; Irawati , Winaika; Rachmawati, Lucky; Fahrullah, A’rasy; Permatasari, Ika; Meidiaswati, Harlina; Wihara, Dhiyan Septa; Arif, Amirul; Mnassri, Yasmine (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to analyze the influence of socioeconomic status and mental health on the academic achievement of final-year students at the Faculty of Economics and Business, Universitas Negeri Surabaya. Method: A qualitative descriptive approach was employed, collecting data through This The study was conducted using a quantitative approach with questionnaires filled out by final-year students. Socioeconomic status was measured using six indicators (education, employment, income, material possessions, services, and transportation), while mental health was measured using five dimensions (happiness, depression, anxiety, emotional control, and positive behavior). Results: Data analysis using multiple linear regression shows that socioeconomic status and mental health have a significant effect, both partially and simultaneously, on students' academic achievement. These results indicate that stable family financial support and healthy psychological conditions can improve the focus, motivation, and learning productivity of final-year students. Novelty: This study provides novelty by integrating two major variables are socioeconomic status and mental health analyzed simultaneously in relation to the academic achievement of final-year university students, a context rarely explored in Indonesian higher education research. Moreover, it applies Bronfenbrenner’s Ecological Systems Theory to explain the interaction between external (socioeconomic) and internal (psychological) factors affecting academic performance, with empirical evidence drawn from final-year students at the Faculty of Economics and Business, Universitas Negeri Surabaya, who are experiencing academic pressure and transition to professional life.